CFD modelling of air temperature distribution inside tunnel greenhouse in semi-arid region. (2018) - Maher, Dhahri; Sami, Ameur; Hana, Aouinet
In the semi-arid region of the southern Mediterranean especially the middle east of Tunisia, one of the main problems of climates is the large diurnal amplitude of temperature, with too low temperature during winter nights and too height temperature during summer day for successful plant growth and development the control of greenhouse environmental parameters is very important. In this work, a computational fluid dynamic software (CFX15.0) was used to study the micro-climate in a 6 × 8 m 2 plastic tunnel. The validity of the computational fluid dynamics (CFD) model was investigated by comparing these results with experimental data collected on strategic days during a period of two months from 1 April to 5 May, 2016. The experiments were conducted in naturally ventilated for two different cases; in close and opening tunnel greenhouse. A very good agreement between experimental and numerical temperature values was verified.